STUDENTS’ ATTITUDES TOWARDS QUIZLET IN ENGLISH VOCABULARY LEARNING - Erlia Novitasari; V Luluk Prijambodo (Magister Scientiae, 2022)
This research reports a study on students’ attitudes towards an online learning platform, Quizlet, in English vocabulary learning. Three research questions were raised, namely: 1) How are the students’ attitudes towards Quizlet in English vocabulary learning? 2) What influence do the students’ attitudes have on their English vocabulary learning using Quizlet? 3) How does Quizlet facilitate the students’ English vocabulary learning? This qualitative study used a questionnaire and an interview to investigate students’ attitudes towards Quizlet in their English vocabulary learning. Twenty students were involved in the questionnaire and six students in the interview. Three major findings are concerned with the students’ attitudes toward Quizlet; the influence of the students’ attitudes towards their English vocabulary learning using Quizlet; and how Quizlet facilitates their English vocabulary learning. Findings indicate that 1) students’ attitudes were all positive, deriving from their opinions, thoughts, feelings, and experiences towards Quizlet; 2) the positive attitudes gave encouragement to their English vocabulary learning; and 3) Quizlet facilitated the students’ English vocabulary learning through its features, namely; Card, Study, Game, and Test modes. Based on these findings, some suggestions are offered. First, for the students to pay more attention to the learning platform they use to learn, such as Quizlet. Second, for the teacher, lecturer, and Study Program Department to pay more attention to the students’ positive attitudes towards a particular learning platform and to utilize more Quizlet for learning. Third, future researchers should investigate how far Quizlet facilitates English vocabulary learning via pretest and posttest.